Trends and Patterns of Utilization in Post-treatment Surveillance Imaging Among Patients Treated for Hepatocellular Carcinoma - Hyder, Omar (2013)
BACKGROUND: Little is known about the patterns of utilization of surveillance imaging after treatment of hepatocellular carcinoma (HCC). We sought to define population-based patterns of surveillance and investigate if intensity of surveillance impacted outcome following HCC treatment. METHODS: The Surveillance, Epidemiology, and End Results-Medicare database was used to identify patients with HCC diagnosed between 1998 and 2007 who underwent resection, ablation, or intra-arterial therapy (IAT). The association between imaging frequency and long-term survival was analyzed. RESULTS: Of the 1,467 patients, most underwent ablation only (41.5 %), while fewer underwent liver resection only (29.6 %) or IAT only (18.3 %). Most patients had at least one CT scan (92.7 %) during follow-up, while fewer had an MRI (34.1 %). A temporal trend was noted with more frequent surveillance imaging obtained in post-treatment year 1 (2.5 scans/year) vs. year 5 (0.9 scans/year; P=0.01); 34.5 % of alive patients had no imaging after 2 years. Frequency of surveillance imaging correlated with procedure type (total number of scans/5 years, resection, 4.7; ablation, 4.9; IAT, 3.7; P<0.001). Frequency of surveillance imaging was not associated with a survival benefit (three to four scans/year, 49.5 months vs. two scans/year, 71.7 months vs. one scan/year, 67.6 months; P=0.01) CONCLUSION: Marked heterogeneity exists in how often surveillance imaging is obtained following treatment of HCC. Higher intensity imaging does not confer a survival benefit.